Insiders’ incentives for asymmetric disclosure and firm-specific information flows - Jiang, Li; Kim, Jeong-Bon; Pang, Lei (Journal of Banking & Finance, 2013)
Recent research suggests that insiders’ incentives for capturing cash flows affect price formation process in which insiders are inclined to withhold good news and to accelerate the release of bad news (Jin and Myers, 2006). We investigate whether insiders’ incentives for private control benefit, proxied by control-ownership wedge, affect firm-specific return characteristics. We find that control-ownership wedge is negatively related to the likelihood of positive return jumps and positively related to the extent of asymmetric market reaction to good news rather than to bad news. Overall, our results support the notion that corporate insiders increase opaqueness and withhold good news in order to capture unexpected cash flow.